The Impact of Misinterpreted Translations in Buyer Comments on Sample Execution in the Pattern and Marker Department - Inggrit Yuliatin (JALILA: Journal of Applied Linguistics and Literary Analysis, 2025)
This study investigates how mistranslated buyer comments affect the accuracy and efficiency of sample making in the Pattern and Marker Department of a garment factory. In global fashion, English is the main language between buyers and suppliers. However, unclear translations caused by incorrect word choices, unfamiliar vocabulary, or poor sentence structure often lead to mistakes in sample making. These issues can slow down production, increase workload, and also reduce the quality of the final product. The research aims to find out what kinds of translation errors happen in buyer comments and how they affect the sample-making process. Using a qualitative descriptive method, the study is based on real work experiences and interviews with staff from pattern, merchandising, and sample teams. Due to confidentiality, actual buyer documents aren’t shown, but the examples reflect real cases. The results show common problems include pragmatic, semantic, syntactic, and lexical errors. For instance, measurement notes are sometimes seen as change requests, terms like "clean finish" are misused, and words like "drop" are taken too literally which leading to wrong patterns and wasted time. The study highlights the need for translators to understand both English and garment-making terms. To reduce errors, it suggests creating internal glossaries, training staff on buyer comment styles, and improving teamwork across departments.